2015
DOI: 10.1038/nmat4369
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for solid-state lithium superionic conductors

Abstract: Lithium solid electrolytes can potentially address two key limitations of the organic electrolytes used in today's lithium-ion batteries, namely, their flammability and limited electrochemical stability. However, achieving a Li(+) conductivity in the solid state comparable to existing liquid electrolytes (>1 mS cm(-1)) is particularly challenging. In this work, we reveal a fundamental relationship between anion packing and ionic transport in fast Li-conducting materials and expose the desirable structural attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

41
1,237
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,250 publications
(1,282 citation statements)
references
References 46 publications
41
1,237
2
2
Order By: Relevance
“…It is notable that the sulphur sublattices (inset of middle panel to Figure 1b) demonstrate an intensely distorted cubic lattice. This anion framework may benefit Na + diffusion followed the mechanism similar to the bcc‐sublattice‐contained superionic conductors described in previous study 10. Different coordinations are observed for these two types of Na + , i.e., Na at Na1 and Na2 sites bound to six and eight sulphur atoms, respectively, as shown in the right panel to Figure 1b.…”
supporting
confidence: 59%
“…It is notable that the sulphur sublattices (inset of middle panel to Figure 1b) demonstrate an intensely distorted cubic lattice. This anion framework may benefit Na + diffusion followed the mechanism similar to the bcc‐sublattice‐contained superionic conductors described in previous study 10. Different coordinations are observed for these two types of Na + , i.e., Na at Na1 and Na2 sites bound to six and eight sulphur atoms, respectively, as shown in the right panel to Figure 1b.…”
supporting
confidence: 59%
“…[24] Trends in knownL i + ion conductors show that a bcc anion framework allows the lowest activation barrier and highest ionic conductivity,b ecause it allows direct Li hops between tetrahedral sites. [30] However,i th as recently been shown in the case of the lithium argyrodites Li 6 PS 5 X (X = Cl, Br,I )t hat the prefactor and the activation energy of ionic conduction are closely linked, and that al ow activation energy alone may not be sufficient to achieve high ion conductivity. [31] In this contribution,w er eport ar e-investigation of cubic aLi 10 P 4 N 10 .B yl owering the synthesis temperature,w eh aves ucceeded in synthesizingt he new polymorph b-Li 10 P 4 N 10 ,a nd have elucidated the phase transition between the a-a nd bpolymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…Many proposed design 'rules of thumb' for fast alkali conductivity, for example, 3D interstitial networks with bottlenecks of sufficient size, 23 the presence of alkali ion disorder, 24 having a polarizable anion framework, 25 body-centered cubic system close-packed anion frameworks, 26 and so on, are limited to specific chemistries or structure types and are not readily generalizable. There has also been limited success in identifying new frameworks that share these features.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al 26 made an interesting observation that both the LGPS and Li 7 P 3 S 11 superionic conductors, which currently have the highest known Li + conductivities of any crystal, possess a bodycentered cubic system-like sulfur framework. Using NEB calculations, Wang et al 26 showed that the direct transition between tetrahedral sites leads to the lowest activation barrier compared with other transitions in close-packed anion frameworks, such as hcp and fcc ( Figure 12).…”
mentioning
confidence: 99%
See 1 more Smart Citation